Optimal control of periodic-review inventory production systems with Weibull deteriorating items - Baten, Md Azizul; Khalid, Ruzelan; Mohd Nawawi, Mohd Kamal (CESER Publications, 2013)
The paper studies of inventory-production systems with two-parameter Weibull distributed deterioration items. The objective of this paper is to determine the optimal production rates and inventory levels that minimize the total cost for the inventory production model.The optimal control theory is applied to solve the developed inventory-production model with Weibull deteriorating items.The solution of the optimal inventory production control model is carried out using the Pontrygin maximum principle.The Lagrangian technique is also used to solve the periodic-review optimal inventory-production model. Finally the numerical examples of the optimal inventory control policy are illustrated through simulation in case of both finite and infinite horizon cases.